An analytical study of the evolution of migrant remittances in developing countries: A case study of Algeria - Zohra, Talhaoui Fatima; Assia, Bourezak; Mohammed, Ben Laria; Samir, Ould Bahammou; Aicha, Omari (International journal of economic perspectives, 2024)
The study aims to analyze the development of remittances in developing countries, which currently represent one of the world’s most important sources of development financing. This is achieved by examining the trajectory of these remittances in developing countries and their significance, particularly for these nations and the world. Additionally, the study highlights Algeria as one of the developing countries that receives a portion of remittances from its migrants, and it explores and analyzes the stages of the temporal development of these remittances in Algeria.